DELONE AND MCLEAN MODELS IN THE IMPLEMENTATION OF ASSET MANAGEMENT INFORMATION SYSTEM ANALYSIS - Dinna Charisma (Sosiohumaniora, 2020)
The study is testing the determinants of physical asset management performance with the approaching Model DeLone and Mclean in the application of The Asset Management Information System (SIMA). The determinant factors studied are the system of quality, top management support, user experience, perceived usefulness, and user satisfaction. This test uses the PLS-SEM (Partial Least Squire - Structural Equation Modeling ). Results of the study indicate that the construct of system quality affects positively and significantly to user satisfaction, while top management support and user experience impact positively and significantly to the perceived usefulness, and perceived usefulness and user satisfaction impact positively and significantly to the physical asset management performance. The final result found that the impact of the implementation of SIMA on the physical asset management performance in BNI has amounted to 69.4%.